Diagnostic value of exosome non-coding RNAs as non-invasive biomarkers in gastric cancer: a meta-analysis - Xu, Qiumiao; Yan, Qinghong; Dai, Zhijiang; Chen, Xiaoting; Liu, Tongwei; Peng, Chengjin; Huang, Guoxin; Liu, Xinyao; Wang, Jingbin (Frontiers in Oncology, 2025)
PurposeGastric cancer, characterised by a significant mortality rate, is one of the most prevalent malignant neoplasms globally. Exosomal non-coding RNAs play a key role in gastric carcinogenesis, metastasis and treatment resistance by regulating gene expression, remodelling the tumour microenvironment and mediating drug resistance. In the identification of early gastric cancer, these exosomal non-coding RNA molecules possess significant potential to be developed into biomarkers that do not entail invasive procedures.MethodsOur study undertook a comprehensive and profound literature examination in core databases like PubMed, Web of Science, ScienceDirect, Embase, Scopus, and Medline, with the aim of precisely evaluating the potential effectiveness of exosomal miRNAs, lncRNAs, and circRNAs in the diagnosis of gastric cancer.ResultsA sum of 52 studies were incorporated, comprising 164 studies. These studies identified a total of 59 miRNAs, 17 lncRNAs, and 16 circRNAs. For miRNAs, sensitivity was estimated at 0.72 (95% CI, 0.69 - 0.76) and specificity at 0.80 (95% CI, 0.77 - 0.83). For lncRNAs, the sensitivity was 0.86 (95% CI, 0.84 - 0.87) and the specificity was 0.82 (95% CI, 0.80 - 0.83). In the case of circRNAs, the sensitivity and specificity were 0.71 (95% CI, 0.63 - 0.78) and 0.88 (95% CI, 0.81 - 0.93) respectively. The AUC for miRNAs was calculated as 0.83. As for lncRNAs, its AUC was established to be 0.89. Regarding circRNAs, the determined AUC was 0.86.ConclusionThese results confirm the efficacy of exosomal ncRNAs as powerful biomarkers for the early diagnosis of gastric carcinomas, thereby laying a strong foundation for the advancement of novel diagnostic approaches.